Xeroderma Pigmentosum with Simultaneous Cutaneous and Ocular Squamous Cell Carcinoma - Effendi RMRA; Fadhlih A; Diana IA; Gondokaryono SP; Dwiyana RF (Dove Medical Press, 2022)
Raden Mohamad Rendy Ariezal Effendi, Azmi Fadhlih, Inne Arline Diana, Srie Prihianti Gondokaryono, Reiva Farah Dwiyana Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin Hospital, Bandung, IndonesiaCorrespondence: Raden Mohamad Rendy Ariezal EffendiDepartment of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin Hospital, Bandung, Indonesia, Email rendy.ariezal.effendi@unpad.ac.idAbstract: Xeroderma pigmentosum (XP) is a rare autosomal recessive disease that disrupts deoxyribonucleic acid (DNA) repair due to ultraviolet (UV) radiation. XP is characterized by extreme sensitivity to sunlight, photophobia, cutaneous lesions in the form of freckle-like hyperpigmented macules, and neoplasia on the skin surface. Malignancy is a common complication found in areas exposed to UV light. Squamous cell carcinomas (SCC) is the most common malignancy seen in patients with XP. This report illustrates a case of XP in a six-year-old girl with cutaneous and ocular SCC. The diagnosis of XP was established based on the patient's history and the presence of typical clinical manifestations. Dermoscopy and histopathology examinations confirmed the presence of SCC on the face and eyes. The management of XP patients includes early diagnosis, lifelong UV protection, and early detection of cutaneous malignancy. Early detection and appropriate management are very important in preventing the occurrence of malignancy.Keywords: dermoscopy, ocular carcinoma, squamous cell carcinoma, xeroderma pigmentosum